2010
DOI: 10.1111/j.1360-0443.2009.02859.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cannabis Use Problems Identification Test (CUPIT): development, reliability, concurrent and predictive validity among adolescents and adults

Abstract: The CUPIT is a brief cannabis screener that is reliable, valid and acceptable for use across diverse community settings and consumers of all ages. The CUPIT has clear potential to assist with achievement of public health goals to reduce cannabis-related harms in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(68 citation statements)
references
References 48 publications
0
65
1
2
Order By: Relevance
“…Similarly, a single episode of use in the past 3 months, coupled with the expression of a ‘strong desire' to use cannabis at least once in the past 3 months, is sufficient to meet the minimum threshold for moderate risk. The consequences of this low threshold are two-fold: many individuals who regularly use cannabis suffer no problems or harms (false positives), while other individuals who consume infrequently do experience harms (false negatives) [7,34,47]. …”
Section: Unpacking ‘Problematic' Cannabis Usementioning
confidence: 99%
“…Similarly, a single episode of use in the past 3 months, coupled with the expression of a ‘strong desire' to use cannabis at least once in the past 3 months, is sufficient to meet the minimum threshold for moderate risk. The consequences of this low threshold are two-fold: many individuals who regularly use cannabis suffer no problems or harms (false positives), while other individuals who consume infrequently do experience harms (false negatives) [7,34,47]. …”
Section: Unpacking ‘Problematic' Cannabis Usementioning
confidence: 99%
“…The CUPIT is composed of two subscales, (1) Impaired Control and (2) Problems. Research on the CUPIT has supported that the CUPIT is both a reliable and valid measure of problematic marijuana use in adolescent and adult samples (Bashford, Flett, & Copeland, 2010). The CUPIT subscales show significant correlations with total counts of Diagnostic and Statistical Manual of Mental Disorders IV (DSM-IV) symptoms of marijuana use disorders (abuse and dependence), as well as a number of other marijuana dependence questionnaires.…”
Section: Cannabis Use Problems Identification Test (Cupit)mentioning
confidence: 99%
“…The CUPIT (Bashford, Flett, & Copeland, 2010) is a brief self-report screening instrument for detection of problematic marijuana use (Appendix F). The CUPIT is composed of two subscales, (1) Impaired Control and (2) Problems.…”
Section: Cannabis Use Problems Identification Test (Cupit)mentioning
confidence: 99%
“…Hence, harnessing a burgeoning variety of innovative technologydelivered interventions [59], public health SEI initiatives should target vulnerable adolescents at risk/on a trajectory to cannabis dependence to arrest transition to more serious harms. Specifically developed and/or validated for adolescent and adult general and clinical populations, appropriate screening tools include the Cannabis Use Problems Identification Test [37] and the SDS [45].…”
Section: Discussionmentioning
confidence: 99%
“…Given both rising consumption and ever-younger initiation worldwide [33,36] cannabis use and disorder trajectories require more comprehensive delineation to expedite recognition of incubating dependence in order to intervene effectively among younger high-risk users. To supplement the sparse literature on the natural history of cannabis use and dependence development, this paper presents data collected in a baseline and 12-month follow-up interview with a mixed adolescent-adult sample of at-risk cannabis users recruited in New Zealand as part of research aimed at developing a brief screener for cannabis problems and reported elsewhere [37].…”
Section: Introductionmentioning
confidence: 99%